1999
DOI: 10.1073/pnas.96.2.453
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of megabase-sized DNA molecules during agarose gel electrophoresis

Abstract: Megabase DNA molecules become trapped in agarose gels during electrophoresis if the electric field exceeds a few volts per cm. Fluorescence microscopy reveals that these molecules invariably arrest in U-shaped conformations. The field-vs.-size dependence for trapping indicates that a critical molecular tension is required for trapping. The size of unligated -ladders, sheared during gel electrophoresis at a given field, coincides with the size of molecules trapped at that field, suggesting that both processes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 31 publications
5
46
1
Order By: Relevance
“…This observation showed that the trapping is reversible which is an important result since it is known that (linear) DNA can become trapped irreversibly at least in agarose gels [30], perhaps by a mechanism involving nicks in the DNA [31]. Reversible trapping of linear DNA has been observed as well, but it only occurs for DNA sizes above about 600 kbp [32].…”
Section: Trapping Is Reversible and Requires Circular Topologymentioning
confidence: 90%
“…This observation showed that the trapping is reversible which is an important result since it is known that (linear) DNA can become trapped irreversibly at least in agarose gels [30], perhaps by a mechanism involving nicks in the DNA [31]. Reversible trapping of linear DNA has been observed as well, but it only occurs for DNA sizes above about 600 kbp [32].…”
Section: Trapping Is Reversible and Requires Circular Topologymentioning
confidence: 90%
“…Extensive modelling was required to convert the measured DNA mobility into effective charge 16,17,[19][20][21][22] 23 , which is remarkable given the complex interplay between hydrodynamics and electrical charges in the screening layer of the DNA. Our data may provide a basis for developing a microscopic theory of the dynamics of ions on DNA.…”
Section: Lettersmentioning
confidence: 99%
“…38 kb (27) and the majority of viral genomes in seawater are Յ50 kb (37), this would explain why we found a small, but statistically insignificant, difference in overall yield of DNA from viruses in the forward-versus back-flushing tests. We presume that the material in the 5-kb ladder that did not enter the gel was of unusually high molecular weight (38). We do not know why this material was recovered with higher efficiency than material of intermediate size in the 60-to ca.…”
Section: Discussionmentioning
confidence: 93%